Pengembangan Pembelajaran Berbasis Web Centric Course pada Materi Stoikiometri untuk Meningkatkan Minat Belajar Siswa di SMA Titian Teras Jambi - Dwi Kurniahayati; Syamsurizal Syamsurizal (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2012)
Recently, Web-based chemistry teaching is becoming a need as support materials for enrichment in chemistry instruction with a variety of learning resources.  The web-based teaching enables both teachers and students to collaborate to explore a variety of learning resources and to address issues of stochiometry through discussion forums both online and offline. This study aims to develop web based learning via web centric course at the stoichiometry topic, taking into account of the learning modalities. The subjects of research were 24 students of Senior high school class XA SMA Negeri Titian Teras Jambi. The results show that the web based model incresase student interest to learn to 27.01%. The tendency of students' interest in utilizing web is positively correlated with the achievement of learning, with a correlation value of 0.62. Thus chemistry instructional through web based learning with regard to learning modalities is effective to enhance students' interests and comprehension of stoichiometry